Tesla in Germany : the most powerful union confronts the most valuable car company - Kinkead, Gwen, 1951-; Baron, James N. (London : Yale School of Management, 2021)
Tesla, the world's most valuable car company, was poised to open a massive new plant in Germany. IG Metall, Germany's largest union, would not let Tesla flout German labor laws and traditions. How the confrontation should be resolved and how it would actually play out were very much at issue.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Tesla Motors -- Case studies; Conflict management -- Case studies; Labor unions -- Germany -- Case studies; Personnel management -- Case studies